A targeted educational programme improves fundamental knowledge of menstrual pain and endometriosis in young women: The Endometriosis Awareness Promotion Project. Issue 6 (December 2022) - Khan, Khaleque N.; Ogawa, Kanae; Iwasa, Koichi; Kuroboshi, Haruo; Okimura, Hiroyuki; Koshiba, Akemi; Manabe, Emiko; Izumi, Mie; Akira, Shigeo; Kashi, Abolfazl Mehdizadeh; Allahqoli, Leila; Tahermanesh, Kobra; et al.
Abstract: Research question: Would a properly designed educational programme offered to young women improve their awareness and fundamental knowledge of menstrual pain and endometriosis? Design: A multinational cross-sectional study using a pen-and-paper questionnaire among women aged 19–24 years was conducted between 2017 and 2019 to assess fundamental knowledge of menstrual pain and endometriosis. Improvement in knowledge was also analysed using a separate questionnaire completed before, and 1–3 months after, a group discussion, lecture on menstrual pain and endometriosis, or both. Results: Among three groups of students (college [ n  = 271], medical [ n  = 877] and nursing [ n  = 763]), knowledge of menstrual pain and endometriosis was lowest among college students, modest among nursing students and fair among medical students ( P < 0.001 for each). The experience of cyclical pain, even when painkillers were taken, was reported by 15.5%, 4.6% and 3.8% of students, respectively. Most students managed their cyclical pain by enduring it or by taking over-the-counter medication. An informative education programme with group discussions, lectures, or both, was successful in improving knowledge and consequences of menstrual pain and endometriosis. Proper education and dissemination of knowledge to college students failed to motivate them to visit gynaecologists; however, medical and nursing students became highly interested in visiting gynaecologists. Conclusions: An educational programme can improve awareness and knowledge of endometriosis and dysmenorrhoea among young women. The programme motivated nursing and medical students, but not college students, to seek medical attention for early detection and management of endometriosis.